On the detection of space-time patterns in squash using dynamical analysis - McGarry, T.; Walter, F. (International Journal of Computer Science in Sport, 2007)
Previous research has interpreted the patterned relations produced from the space-time interactions of squash players as a dynamical system. Importantly, the theoretical basis for pattern formation within dynamical systems is predicated upon the shared information exchanges among the parts that comprise them. Thus, the patterned dynamics of a squash rally are the supposed product of shared information (meaningful interactions) of the squash dyad instead of the random interactions that might otherwise be expected to occur from the happenstance pairing of two independent squash players. To investigate the squash dyad for this essential feature of a dynamical system, four data sets of 47 trials were created. Each trial within a data set comprised the individual movements of a number of independent squash players, or distracters (N = 2, 2, 4 and 6 for the four data sets, respectively), as well as the individual movements of two squash players taken from the same squash rally. Thus, a trial within a given data set comprised of a number of distracters (two, four or six) as well as a squash dyad (two players). The question of interest was whether the squash dyad could be identified from the trial using dynamical analysis techniques. To this end, all pair-wise comparisons for all trials were subjected to dynamical analyses and the subsequent outputs were then used to identify the squash dyads using predetermined criteria. The results demonstrated that the outputs from the dynamical analyses were successful in identifying the squash dyad from the distracters well beyond chance expectations for all data sets. These findings were interpreted as compelling evidence that the dynamical features of the squash dyad, as reported in previous research, are indeed the result of shared information exchanges among the players as consistent with dynamical systems theory.